Influence of HIV infection and the use of antiretroviral therapy on selenium and selenomethionine concentrations and antioxidant protection - Watanabe, Lígia Moriguchi [UNESP]; Barbosa Júnior, Fernando; Jordão, Alceu Afonso; Navarro, Anderson Marliere (Elsevier, 2016)
Objective The aim of the present study was to evaluate whether HIV infection and antiretroviral therapy (ART) use are associated with oxidative stress, concentrations of selenium and selenomethionine, and antioxidant protection. Methods Individuals were classified as HIV negatives: control group (CG; n = 40); HIV positives: group 1 (G1; taking ART for >5 y, n = 40) and group 2 (G2; taking ART for <5 y, n = 40). Plasma and erythrocyte selenium, selenomethionine, glutathione (GSH), glutathione peroxidase activity (GPX), and malondialdehyde (MDA) were evaluated. Results Selenium deficiency (plasma selenium 45 μg/L) was not observed in any of the participants, and plasma selenium in CG (69.4 μg/L) was lower than in G1 and G2 (88.4 and 72.5 μg/L, respectively). G1 and G2 showed higher concentrations of MDA and GPX and lower concentration of GSH than CG. Multiple linear regression analysis indicated an association of MDA, GPX, and GSH with HIV status. CG participants showed higher concentrations of selenomethionine than G1 and G2 individuals and we observed a significant negative correlation between the concentration of selenomethionine and the use of ART. Conclusions Prolonged ART use seems to increase the selenium in plasma, but influences the reduction of selenomethionine. HIV infection was associated with increased oxidative stress and appears to affect in protective activity of GPX. Finally, more studies are required to further address the importance of selenium and selenometabolites in the pathogenesis of infection and metabolism of HIV-positive individuals in prolonged use of ART.
Keywords: Antiretroviral therapy; HIV; Oxidative stress; Selenium; Selenomethinine